Предмет: Математика,
автор: 202456
упростите 2*(3х-1)-4*(2х+3) при х=0.5
зарание спасибо
Ответы
Автор ответа:
0
2(3х-1) - 4(2х+3) = 6х-2 -8х-12= -2х-14= -2(х+7)
при х=0,5
-2 (0,5 +7) = -2 *7,5 = - 15
при х=0,5
-2 (0,5 +7) = -2 *7,5 = - 15
Автор ответа:
0
6х-2-8х+12
6х-8х=–2х
-2+12=10
-2х+10
Х=0,5 (0,5*2=1)
-1+10=9
6х-8х=–2х
-2+12=10
-2х+10
Х=0,5 (0,5*2=1)
-1+10=9
Похожие вопросы
Предмет: Английский язык,
автор: tomkovicvika
Предмет: Физика,
автор: evaschemelina
Предмет: Английский язык,
автор: zhenyafedorisch
Предмет: Литература,
автор: gerakoz
Предмет: Математика,
автор: 89625759665